Recent progress in crash pulse analysis. (29th October 2004) - Gearhart, Chris
The deceleration of the occupant compartment of a vehicle during a crash, also known as the crash pulse, is of central importance in the analysis of vehicle safety. The crash pulse is used to assess the crashworthiness of the vehicle structure and as input to occupant injury models. This paper provides a brief historical review of crash pulse analysis based on simple polynomial and Fourier characterisations, and presents some recent developments in experimental crash pulse characterisation based on statistical wavelet analysis. A simple formalism for decomposing the crash pulse, obtained from computational models, into component contributions is discussed and analysed for a simple spring-mass model of vehicle structure. Implications for more detailed models are discussed. Finally, a possible method for connecting occupant injury to the component level crash pulse contributions is presented.